Analisis Keperilakuan Wajib Pajak Dalam Membayar Pajak Kendaraan Bermotor Di Kota Denpasar - Setiawan, Putu Agus; Ayu, Putu Cita; Pramuki, Ni Made Wisni Arie (UNHI Press, 2025)
This research aims to examine and analyze taxpayer behavior in paying motor vehicle tax in Denpasar City. The theory underlying this research is the Theory of Planned Behavior (TPB). The population in this study were taxpayers registered at the Denpasar City Samsat office with a total of 835,311 taxpayers. The sampling method in this research is non-probability sampling using convenience sampling techniques. that happened to be found suitable as a data source. To be able to determine the number of samples in research, it can be calculated using the Slovin formula, so that a sample of 100 respondents is obtained. Data analysis techniques using SEM (structural equation modeling). The research results show that attitude has an insignificant positive effect on taxpayers' intention to pay motor vehicle tax. Subjective norms have a positive and significant effect on taxpayers' intentions to pay motor vehicle taxes. Perceived behavioral control has a positive and insignificant effect on the intention to pay motor vehicle tax. Perceived behavioral control has a positive and significant effect on taxpayer compliance behavior in paying motor vehicle taxes. Intention to pay taxes has a positive and significant effect on taxpayers' compliant behavior in paying motor vehicle taxes.